Synthesis of a flame retardant substance based on liquid glass and silicagel - Khafiz Ibroimovich Akhmedov (Science and Education, 2024)
In this work, the synthesis, analysis, and application of a refractory substance obtained on the basis of cremnisol and liquid glass were studied in laboratory conditions. Also, the IR spectroscopic analysis of this substance and the fire resistance property of the sample treated with a solution of a refractory substance were studied. In addition, electron microscopic analyzes of the refractory material are emphasized.